Sequences in the visna virus long terminal repeat that control transcriptional activity and respond to viral trans-activation: involvement of AP-1 sites in basal activity and trans-activation. - Hess, J L (1989)
Visna virus is a pathogenic lentivirus of sheep whose gene expression is developmentally regulated in cells of the monocyte-macrophage lineage. Gene expression directed by the visna virus long terminal repeat (LTR) is increased in infected cells by a virus-encoded trans-acting protein. trans-Activation is mediated in part by increases in the steady-state level of mRNA. Deletion and linker-scanner mutants were constructed to locate sequences in the LTR that regulate transcription and are responsive to viral trans-activation. The activities of these mutants were tested by using them to drive transcription of the bacterial gene for chloramphenicol acetyltransferase in transient expression assays. Three regions located between-140 and the cap site were found to be important for basal transcriptional activity, and the importance of each region was found to be dependent on the cell type. Sequences responsive to viral trans-activation were found to be the same sequences required for basal transcriptional activity. The visna virus LTR contains six sequences that are homologous to the recognition site for cellular transcriptional factor AP-1 and a single sequence homologous to the recognition site for transcriptional factor AP-4. Both of these classes of binding sites appear to be important for regulating the basal level of transcription of visna virus. The AP-1-binding site most proximal to the TATA box was found to be one target for viral trans-activation. The visna virus promoter was found to be activated by serum; this serum response has also been mapped to the AP-1-related sequences in the LTR.